Headteachers’ Leadership Orientation Frames And Intentions Towards Implementing Nutrition Education - Ahmed, Fozia (2020)
In this study, the leadership orientations frames of secondary school headteachers in Baluchistan province of Pakistan, were examined in relation to their intentions towards implementing nutrition education. Leadership orientation survey (LOS) and newly developed intention questionnaire (based on the theory of planned behavior) were used to collect data from 378 (152 females and 226 males) secondary school headtachers. The study sought to determine if there existed a relationship between headteachers’ leadership orientation frames and their intentions towards implementing nutrition education.